Mecânica Relacional: A Propósito de uma Resenha - Escobar, O.; Pleitez, V. [UNESP] (Sociedade Brasileira de Física, 2001)
We present a critical analysis of what is called Relational Mechanics, as it has been presented in a book thus entitled, which has been recently reviewed in this journal.

Neste artigo fazemos uma análise crítica à proposta da Mecânica Relacional tal como apresentada no livro de mesmo nome, objeto de uma resenha recente nesta revista.
Relational Mechanics: Concerning a book review